2021
DOI: 10.1111/jdv.17027
|View full text |Cite
|
Sign up to set email alerts
|

Early efficacy and safety data with fixed‐dose combination calcipotriol/betamethasone dipropionate foam attributed to mechanism of absorption and steroid potency

Abstract: Topical therapy is the mainstay of treatment for the majority of patients with psoriasis vulgaris (chronic plaque psoriasis), with combinations of vitamin D analogues and glucocorticoids having been shown to negate many of the negative effects associated with either monocomponent individually. Following the established efficacy of fixed‐dose combination calcipotriol (Cal; 50 µg/g) plus betamethasone dipropionate (BD; 0.5 mg/g) ointment and gel formulations, a novel Cal/BD foam formulation was developed. When a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…While Cal/BD foam is one of the staple treatments for cutaneous psoriasis, 48 only one RCT has investigated this product for PND, reporting a reduction in NAPSI of 44% after 12 weeks of daily application. 4 The notably higher efficacy rates in our study after 24 weeks of treatment (−76% N‐NAIL, −68% NAPSI) with comparable safety profile and improvement in PROMs indicate a favorable risk–benefit ratio for prolonged treatment with Cal/BD foam.…”
Section: Discussionmentioning
confidence: 99%
“…While Cal/BD foam is one of the staple treatments for cutaneous psoriasis, 48 only one RCT has investigated this product for PND, reporting a reduction in NAPSI of 44% after 12 weeks of daily application. 4 The notably higher efficacy rates in our study after 24 weeks of treatment (−76% N‐NAIL, −68% NAPSI) with comparable safety profile and improvement in PROMs indicate a favorable risk–benefit ratio for prolonged treatment with Cal/BD foam.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the Cal/BD foam, as compared to gel or ointment, revealed higher skin penetration, better cosmetic qualities, and higher efficacy. 11 On top of that, foam did not increase the risk of side effects. 5 Factors with a positive effect on adherence include also the good patient-doctor relation, patient education, follow-up visits after treatment completion and patient participation in therapeutic decisions.…”
Section: Medications Used In Long-term Topical Therapy Of Psoriasismentioning
confidence: 97%
“…The most recent drug forms are foams. It was shown that the Cal/BD foam, as compared to gel or ointment, revealed higher skin penetration, better cosmetic qualities, and higher efficacy 11 . On top of that, foam did not increase the risk of side effects 5 .…”
Section: Medications Used In Long‐term Topical Therapy Of Psoriasismentioning
confidence: 99%
“…16 Propellants contained in the foam formulation evaporate rapidly and lead to the formation of a thin supersaturated layer on the skin increasing the penetration and the bioavailability of active ingredients Cal/BD. 17,18 In addition to data showing the superiority of Cal/BD foam over its individual components and Cal/BD ointment and gel formulations, the early efficacy of Cal/BD foam was demonstrated in the treatment of psoriasis flare-ups.…”
Section: Short Term Efficacymentioning
confidence: 99%